La tentation du socialisme au Bénin - Genné, Marcelle (Études internationales, 1978)
The achievement of scientific socialism as conceived by MM. Ch. Bettelheim, J. Charrière and H. Marchisio is based on four general principles, namely : the taking of power by proletarian party ; the establishment of the dictatorship of the proletariat ; the public ownership and control of the economy ; and agricultural reform. Relating the experience of Benin to these fundamental principles shows that there are different paths to socialism. Accordingly, the accumulation of different facts leads to a revision of the theory of scientific socialism.